The Transition to Bioeconomy - Vasile Dinu (Amfiteatru Economic)
Developed and developing countries face social, economic and environmental challenges. These are the dimensions of sustainability, and the future of mankind depends on the transition from a linear economy towards bioeconomy. This shift represents a challenge for the EU itself due to several factors, such as the economic disparities between the Member States, the lack of concrete national and regional bio-economic strategies, their poor application and correlation, etc. At the same time, within the contemporary period, this transition is one of the most important priorities in the world, capturing the attention of political decision-makers, industry representatives and researchers.